2023
DOI: 10.1021/acs.inorgchem.3c02712
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for Luminescent Titanocenes: Improving the Photoluminescence and Photostability of Arylethynyltitanocenes

Matilda Barker,
Thomas J. Whittemore,
Henry C. London
et al.

Abstract: Complexes that undergo ligand-to-metal charge transfer (LMCT) to d0 metals are of interest as possible photocatalysts. Cp2Ti­(C2Ph)2 (where C2Ph = phenylethynyl) was reported to be weakly emissive in room-temperature (RT) fluid solution from its phenylethynyl-to-Ti 3LMCT state but readily photodecomposes. Coordination of CuX between the alkyne ligands to give Cp2Ti­(C2Ph)2CuX (X = Cl, Br) has been shown to significantly increase the photostability, but such complexes are not emissive in RT solution. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
1
0
0
Order By: Relevance
“…13,17,126 Very few complexes with emissive LMCT excited states are known and of those, most are short-lived and/or only emissive at low temperatures. 20,49,50,56,66,70,74,76,78,86,127–129 Computational studies propose their low energy emission stems from a mixed 3 LMCT/ 3 LLCT excited state where the ground state is entirely ligand-based and the excited state exhibits mixed metal and ligand character, consistent with the experimentally observed long-lived excited state. 22,47 Interestingly, spectroscopic studies further deciphered the origin of this photoluminescence and found Zr(PDP) 2 complexes exhibit thermally activated delayed fluorescence whereupon reversible intersystem crossing enables emission from both the singlet and triplet states across a range of temperatures.…”
Section: Photochemical Reactivity From Lmct Excited Statessupporting
confidence: 65%
“…13,17,126 Very few complexes with emissive LMCT excited states are known and of those, most are short-lived and/or only emissive at low temperatures. 20,49,50,56,66,70,74,76,78,86,127–129 Computational studies propose their low energy emission stems from a mixed 3 LMCT/ 3 LLCT excited state where the ground state is entirely ligand-based and the excited state exhibits mixed metal and ligand character, consistent with the experimentally observed long-lived excited state. 22,47 Interestingly, spectroscopic studies further deciphered the origin of this photoluminescence and found Zr(PDP) 2 complexes exhibit thermally activated delayed fluorescence whereupon reversible intersystem crossing enables emission from both the singlet and triplet states across a range of temperatures.…”
Section: Photochemical Reactivity From Lmct Excited Statessupporting
confidence: 65%